Intermediaç\~ao estatal nas exportaç\~oes de equipamentos militares: As experiências da Rússia e da França - Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The purpose of this article is to analyze the experiences of Russia and France regarding the state brokerage in the exports of weapons. Such activity is essential to maintain their defense industries' viability, given the dependence that both have on the foreign market. Some of the experiences of these two countries may be a source of lessons for Brazil, at a time when the Brazilian government signals the creation of an institutional arrangement dedicated to carrying out these activities. In the analysis, it was observed that the institutional frameworks for the state brokerage in Russia and France are quite distinct, especially if one considers the greater degree of centralization of such activities in Russia. However, a common element is the provision of "packages" of products, services, funding and offsets - and this seems to be an important element in the conquest/ maintenance of markets in this sector.
Keywords: F52; 330; arms exports; defense industry; state brokerage; trading; offsets; Rosoboronexport; Direction générale de l'armement (DGA)